(untitled) (Research, Society and Development, 2021)
Objective: To analyze the body composition, behavior of cardiovascular variables and autonomic HR modulation after a high power focused ultrasound application in women with localized abdominal fat and overweight. Methods: Twenty-three women participated (21.3 ± 3.06 years), presenting at least 1.5 cm of abdominal skin fold, using oral contraceptive and sedentary. A visit was made to the aesthetic center, where the initial anthropometric assessments were performed, and before and after the application of the therapy, the body composition (bioimpedance), blood pressure (BP) and autonomic assessment were evaluated. The indices (RMSSD, SDNN) and (HF, LF un and ms2) were analyzed. For the analysis of the effects on body composition, BP variables and cholesterol values and autonomic modulation at rest and recovery moments found in the pre and post-intervention moments, Student’s t-test or Wilcoxon test were applied. with Dunn’s post-test for non-normal distribution data, and effect size was calculated using Eta-squaredd and p <0.05 for all tests. Results: The acute effect observed after the focused ultrasound therapy did not promote significant differences in the pre and post comparisons of the studied variables; however, there was a tendency in the increase of the indices (SDNN, SD2) and (rMSSD, SD1 and HF ms2 and un) in the moments of recovery compared to the moment of rest. Conclusion: A session of focused high power ultrasound therapy did not promote significant changes in body composition, blood pressure values, autonomic modulation of FV and cholesterol values.